Institutional barriers to food safety: The irrigated vegetable value chain in Accra, Ghana - Galibourg, David; Scott, R. E.; Gough, K. V.; Amoah, Philip (PLOS, 2025)
The faecal contamination of irrigation water threatens public health. Although safe practices can mitigate hygiene and food safety risks along the urban irrigated vegetable value chain, their adoption remains limited. A behaviour framework was combined with a participatory approach to explore how institutions influence stakeholders’ capability, opportunity and motivation to adopt safe practices in Accra, Ghana. After extensive preparation, a dialogue engaged stakeholders and institutions in identifying the actors and interactions influencing stakeholder practices. We found that institutional dynamics and misaligned priorities hinder stakeholders’ opportunity and motivation to adopt safe practices, while their capability (education and skills) is not actively hindered. Knowledge gaps created by top-down approaches and sectoral silos were bridged by engaging participants in conducting the behavioural diagnosis. This shared understanding highlights the need to integrate and harmonise policies, regulations and service provision across water, sanitation, agriculture and health sectors, enabling participants to co-design arrangements that make safe practices easier to adopt.